Analysis of the Impact of Computer Technology Development on the Education System - Alwendi; Andi Saputra Mandopa; Lela Budiarti (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
The development of computer technology from time to time has brought significant changes in various aspects of life, including the education system. This study aims to analyze the impact of the evolution of computer technology on the education system, especially in terms of learning methods, access to information, and efficiency of educational administration. The problems raised in this study are the extent to which computer developments affect the education system and how the integration of these technologies can improve the quality of learning. This study uses a qualitative descriptive method with a literature study approach and field observations in several universities. Data were collected through interviews with lecturers and education staff, as well as documentation related to the use of computer technology in the education process. The results of the study show that the development of computer technology has a positive impact on the education system, including through bold learning, the use of the Learning Management System (LMS), and the digitalization of campus administration. However, the study also identified challenges in its implementation, including gaps in access and technological skills. Thus, adaptation to computer developments must be accompanied by training and infrastructure improvements so that the benefits can be felt evenly.